Tertiary cross-linked and weighted fracturing fluid enables fracture stimulations in ultra high pressure and temperature reservoir. (15th May 2020) - Yang, Xiaojiang; Mao, Jincheng; Zhang, Wenlong; Zhang, Heng; Zhang, Yang; Zhang, Chong; Ouyang, Dong; Chen, Qiang; Lin, Chong; Zhao, Jinzhou
Highlights: An excellent CHKO2 weighted fracturing fluid with density of 1.33 g/cm 3 was developed. Tertiary release strategy realized high temperature resistance by successive cross-linking. The weighted system can realize delayed cross-linking and the time is adjustable. Acidic breaker realized complete gel breaking under the strong reducing environment. Abstract: Advancement of exploration and drilling extended the depth of oil and gas reservoir development, while it is accompanied by great challenges of abnormally high pressure and ultra-high temperature. Weighted fracturing fluid was considered as one of the key technologies to deal with this challenge in the case of existing fracturing equipment. In this work, a super guar gum with good solubility was modified from guar gum for potassium formate (CHKO2 ) weighted fracturing fluid and tertiary cross-linking strategy was employed to cope with ultra-high reservoir temperature. In addition, a novel gel breaker which was completely different from the conventional oxidized breaker was designed to achieve the complete gel breaking under strong reducing conditions caused by concentrated CHKO2 . The CHKO2 weighted fracturing fluid proposed in this study performed very well in static leak-off and formation damage. The density of fracturing fluid weighted by CHKO2 here was up to 1.33 g/cm 3 . The applicable temperature of the fluid can reach 180 °C and the fracturing fluid can be completely broken, almost with no residue left after the operation. This is a very useful and practical technology for abnormally high-pressure and ultra-high temperature reservoir stimulation.